Multi-attribute decision by sampling: an account of the attraction, compromise and similarity effects - Ronayne, D; Brown, G (Elsevier, 2017)
Consumers’ choices are typically influenced by the choice context in ways that standard models cannot explain. We provide a concise explanation of the attraction, compromise and similarity effects. The model, Multi-Attribute Decision by Sampling (MADS) posits that the evaluation of a choice option is based on its relative position in the market distribution as first inferred and then sampled by the decision-maker. The inferred market distribution is assumed to be systematically influenced by the choice options. The value of a choice option is assumed to be determined by the number of sampled comparators that the option dominates. We specify conditions on the sampling distribution that are sufficient for MADS to predict the three context effects. We tested the model using a novel experimental design with 1,200 online participants. In the first experiment, prior to making a choice participants were shown a selection of market options designed to change their beliefs about the market distribution. Participants’ subsequent choices were affected as predicted. The effect was strong enough to impact the size of two of the three classic context effects significantly. In the second experiment, we elicited individuals’ estimates of distributions of market options and found the estimates to be systematically influenced by the choice set as predicted by the model. It is concluded that MADS, a model based on simple binary ordinal comparisons, is sufficient to account for the three classic context effects.